PENURUNAN EMISI POLUTAN KAMBING PERANAKAN ETAWAH YANG DIBERI WAFER RANSUM LIMBAH INKONVENSIONAL MELALUI APLIKASI TEKNOLOGI BIOFERMENTASI DAN SUPLEMENTASI - Partama, Ida Bagus Gaga; Mudita, I Made (Jurnal Veteriner, 2019)
A Research had been carried out to reduce the pollutant emission of the Ettawa Crossbreed Goat given ration non-conventional waste at Farm of Animal Husbandry Faculty Udayana University, Bukit Jimbaran. Bio-fermentation of rumen liquor (1.5% and 3.0%) and supplementation of pignox as source of multivitamin-mineral (0.15% and 0.30%) and Animal Fat “Tallow” (5% and 10%) were applied in this experiment. Fifteen Goat of Ettawa Crossbreed were used in this experiment which designed of Randomized Block Designed with five treatments and three blocks. The treatments were; WFS 0 are ration unconventional waste without bio-fermentation and supplementation, WF 1 S 11 are WFS 0 fermented by 1.5% rumen liquor and supplemented by 0.15% multivitamin-mineral and 5 % Tallow, WF 2 S 12 are WSF 0 fermented by 3,0% rumen liquor and supplemented by 0.15% multivitamin-mineral dan 10 % Tallow, WF 1 S 21 are WFS 0 fermented by 1.5% rumen liquor and supplemented by 0.30% multivitamin-mineral and 5 % Tallow and WF 2 S 22 are WFS 0 fermented by 3.0% rumen liquor and supplemented by 0.30% multivitamin-mineral and 10 % Tallow. The result showed that application of bio-fermentation and supplementation technology  (WF 1 S 11 , WF 2 S 12 , WF 1 S 21 and WF 2 S 22 ) were significant decreased (P<0.05) the concentration and production methane emission each totally VFA are 18.57 – 39.57% and 20.15 – 40.45%, production of CO 2 each totally VFA are 2.51 – 13.29%, production of fecal ammonia (42.59–61.11%) and percentage of production fecal ammonia each g crude protein consumption (10.20–51,02%) compared with WFS 0, in spite of concentration of CO 2 in rumen fluid, concentration and production urine ammonia were similar (P>0.05) in all treatments. Goat were given WF 1 S 11 produced fecal ammonia each day and percentage of production fecal ammonia each g consumption of crude protein were lowest (P<0.05) are 0.021 Vs 0.024-0.054 g/d and 0.024 Vs 0.033-0.049%, even though lowest methane concentrations, production of methane and CO 2 emmision each mM total VFA produced by WF 1 S 21 were 13.376 Vs 17.410-28.762 mM; 19.738 Vs 20.850-33.147 % and 45.657 Vs 46.720–52.655%. It was concluded that; 1) Application of bio-fermentation and supplementation technology in  ration unconventional can reduce pollutant emission of the ettawa crossbreed goat, 2) Bio-fermentation of 1.5% rumen liquor and supplementation of 0.15 – 0.30% multivitamin-mineral and 5% Tallow in the ration unconventional waste can lowest produced of NH 3 fecal each crude protein consumption, CH4 concentration, production of CH 4 and CO 2 each mM total VFA of rumen fluid.